SYSTEM FOR MONITORING OF TECHNICAL CONDITION OF SHAPED PROFILES OF METAL STRUCTURES OF BUILDINGS - FILIPPOVA, MARYNA; DEMCHENKO, MARIIA; BOHDAN, HALINA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article considers the relevance of implementing a system for monitoring the technical condition of metal structures of buildings, which is primarily related to the increase in the use of metal profiles as the main structural elements. The configuration of buildings, which directly depends on the architectural form of the building itself, becomes complicated and requires mandatory monitoring of its elements. Monitoring is carried out for compliance of the building parameters with the specified limits within the permissible values of stresses that arise under the action of loads.  The main methods used to determine the stress-strain state of metal structures, based on the structural features of shaped profiles, which act as the main structural elements - beams in metal structures of buildings, are considered.  The applicability of the acoustic method, which is based on the use of the acoustoelastic effect, namely the connection of the elastic properties of materials with a change in the character of the propagation of ultrasonic waves, to determine the actual stress-strain state of shaped profiles has been evaluated. The expediency of using sounding according to the scheme of the mirror-shadow method, which allows to increase the length of passage of the ultrasonic wave in the shelf along the linearly distributed stresses, is shown. The possibility of determining the actual values of mechanical stresses in the shaped profiles of metal structures by measuring the time intervals of the passage of the ultrasonic wave and the temperature in the measurement area is shown. The functional scheme of the system for monitoring the technical condition of buildings is presented, which incorporates the acoustic method of establishing the stress-strain state of metal structures.  The main components of the monitoring system and the possibilities of its hardware implementation, by means of wireless data transmission, which is intended for installation in buildings that are in operation and still being designed, are considered.
Keywords: stressed deformed state; acoustic control; metal structures; LoRaWAN networks